Knowledge, attitude and utilization of oral cholera vaccine in Bauchi Metropolis, Bauchi State, North-Eastern Nigeria - M. Maigoro, Aliyu; U. Ibrahim, Khadija; S. Usman, Usman; Abdullahi, Ibrahim A.; Shehu, Ado (International Journal Of Community Medicine And Public Health, 2024)
Background: Since early 1800s, pandemics of cholera have affected millions of people around the world. It is estimated that 1.3 to 4.0 million cases of cholera and 21 000 to 143 000 deaths occurs each year due to cholera worldwide. Nigeria had suffered large cholera epidemics in recent years. The study determined the knowledge, attitude and utilization of Oral Cholera Vaccines (OCV) in Bauchi metropolis, Bauchi state, Nigeria. Methods: The design was a descriptive cross sectional study and a multistage sampling technique was used in collecting data from 372 respondents using semi-structured, interviewer administered questionnaires. Data were analyzed using SPSS version 26 at 5% significance level and 95% confidence interval. Results: The study revealed that majority of the respondents 328 (88.2%) knew about OCV and their commonest source of information was radio 120 (34.7%). More than half of the respondents 239 (64.2%) have heard of the house to house OCV campaign. Attitudes were partially negative, because more than half 198 (53.2%) believed that oral cholera vaccine is unsafe for ill persons. Practices were relatively poor because out of the 372 respondents, 201 (54.0%) received OCV, 225 (60.4%) didn’t know when to receive the second dose and 225 (60.5%) didn’t receive the second dose. Conclusions: The respondents had fairly good knowledge about OCV use, but with negative attitude which could have led to the poor practice. We recommend that the government should reinforce education to the public on the importance of OCV use in prevention of cholera.